Bienestar psicológico, optimismo y resiliencia en mujeres con cáncer de mama - Guil, Rocío; Zayas, Antonio; Gil-Olarte, Paloma; Guerrero, Cristina; González, Silvia; Mestre, José Miguel (Psicooncología, 2016)
Objective: To evaluate the relationship between Perceived Psychological well-being, Optimism and Resilience in women survivors of breast cancer.Method: The sample was composed of 30 women diagnosed with breast cancer who were undergoing adjuvant treatment in Oncology Units General Hospital of Jerez de la Frontera and the University Hospital Puerta del Mar (Cadiz). The average age was 47.47 years (SD = 6,356) and the average of months from diagnosis of the disease was 9.93 (SD = 8,541). Scale of Psychological Well-being administered Perceived Ryff (1989), the Life Orientation Test Revised (LOT-R) Scheier, Carver and Bridges (1994) and the Scale of Resilience Wagnild and Young (1993) to assess psychological well-being the dispositional optimism and resilience respectivelyResults: Descriptive analyzes show that women diagnosed with breast cancer have levels of psychological well-being, dispositional optimism and higher than the average values provided by Resilience scales. On the other hand, regression analyses revealed that only some of the dimensions of resilience allowed to explain and predict some dimensions of psychological wellbeing, not dispositional optimism.Conclusions: The results seem to confirm the idea that if the capacity of women with breast moderate negative affect generated by the diagnosis itself and the consequences of their cancer treatment works and to promote their adaptation to the new situation we can contribute to increasing psychological well-being.
Keywords: Breast cancer; optimism; resilience; well-being.